A ligand strand that displays anion-dependant reactivity with acetonitrile; formation of either a mononuclear complex or head-to-tail circular helicate. Issue 23 (22nd May 2019) - Clemett, Christopher J.; Faulkner, Robert A.; Rice, Craig R.; Slater, Christopher; Wedge, Christopher J.; Whitehead, Martina
Abstract : The ligandL 2, 2 contains two bidentate domains separated by a 3, 3-diamino-2, 2′-biphenyl spacer unit and with Cu(ClO4 )2 a mononuclear species is formed ( e.g. [Cu(L 2, 2 )] 2+ ). Abstract : The ligandL 2, 2 contains two bidentate domains separated by a 3, 3-diamino-2, 2′-biphenyl spacer unit and with Cu(ClO4 )2 a mononuclear species is formed ( e.g. [Cu(L 2, 2 )] 2+ ). Upon coordination with Cu(triflate)2 the ligand undergoes reaction with an acetonitrile solvent, producing a different ligand with unsymmetrical bidentate and tridentate domains (L 2, 3 ). This new ligand results in the formation of a tetranuclear head-to-tail circular helicate [Cu4 (L 2, 3 )4 ] 8+ showing that in the presence of the triflate anion the ligand denticity is changed.